Riparian reserves help protect forest bird communities in oil palm dominated landscapes. Issue 6 (6th August 2018) - Mitchell, Simon L.; Edwards, David P.; Bernard, Henry; Coomes, David; Jucker, Tommaso; Davies, Zoe G.; Struebig, Matthew J.
Abstract: Conversion of forest to oil palm agriculture is a significant and ongoing threat to tropical biodiversity. Despite this, little is known about the value of riparian reserves in oil palm and how these conservation set‐asides might best be managed to maintain biodiversity. We characterized bird communities of 28 sites in an oil palm‐forest mosaic in Sabah, Malaysia using 6, 104 encounters from 840 point counts. Sites included oil palm riparian reserves of various vegetation quality and reserve widths, which were compared to oil palm streams without a riparian reserve as well as riparian and nonriparian control areas in continuous logged forest. Riparian reserves, oil palm waterways, and control sites in riparian and nonriparian forest supported distinct avifaunal communities. Riparian reserve width, forest quality, and amount of forest cover were the strongest predictors of bird species richness. For forest‐dependent species, each of these predictors had a stronger effect size when compared with all species. On average, reserves held 31% of all species and 30% of forest specialists, whereas riparian forest controls averaged 32% of all species, but 38% of forest species. Riparian reserves with >40 m of natural vegetation on each bank supported similar bird diversity to riparian forest control habitats found in continuous forest. However, to support equivalent numbers of forest‐dependent species and species of conservation concern, reserves would need to be at least 100‐m wide on each bank. The largest numbers of species were found in riparian reserves with above‐ground carbon densities exceeding 75 tC/ha, highlighting the importance of forest quality, as well as width, in supporting riparian bird communities. Synthesis and applications . If designed and protected appropriately, riparian reserves in oil palm estates support diverse bird communities, including many species of conservation concern. This can be achieved by designating large reserves (80–200 m total width). But, to maximize species numbers, forest disturbance should also be minimized prior to conversion as well as during plantation operations. Abstract : If designed and protected appropriately, riparian reserves in oil palm estates support diverse bird communities, including many species of conservation concern. This can be achieved by designating large reserves (80–200 m total width). But, to maximize species numbers, forest disturbance should also be minimized prior to conversion as well as during plantation operations.